Growth Hormone (GH)-dependent expression of a natural antisense transcript induces zinc finger E-box-binding homeobox 2 (ZEB2) in the glomerular podocyte: A novel action of GH with implications for the pathogenesis of diabetic nephropathy - P. Anil Kumar (2018)
Growth hormone (GH) excess results in structural and functional changes in the kidney and is implicated as a causative factor in the development of diabetic nephropathy (DN). Glomerular podocytes are the major barrier to the filtration of serum proteins, and altered podocyte function and/or reduced podocyte number is a key event in the pathogenesis of DN. We have previously shown that podocytes are a target for GH action. To elucidate the molecular basis for the effects of GH on the podocyte, we conducted microarray and RT-quantitative PCR analyses of immortalized human podocytes and identified zinc finger E-box-binding homeobox 2 (ZEB2) to be up-regulated in a GH dose- and time-dependent manner. We established that the GH-dependent increase in ZEB2 levels is associated with increased transcription of a ZEB2 natural antisense transcript required for efficient translation of the ZEB2 transcript. GH down-regulated expression of E- and P-cadherins, targets of ZEB2, and inhibited E-cadherin promoter activity. Mutation of ZEB2 binding sites on the E-cadherin promoter abolished this effect of GH on the E-cadherin promoter. Whereas GH increased podocyte permeability to albumin in a paracellular albumin influx assay, shRNA-mediated knockdown of ZEB2 expression abrogated this effect. We conclude that GH increases expression of ZEB2 in part by increasing expression of a ZEB2 natural antisense transcript. GH-dependent increase in ZEB2 expression results in loss of P- and E-cadherins in podocytes and increased podocyte permeability to albumin. Decreased expression of P- and E-cadherins is implicated in podocyte dysfunction and epithelial-mesenchymal transition observed in DN. We speculate that the actions of GH on ZEB2 and P- and E-cadherin expression play a role in the pathogenesis of microalbuminuria of DN. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.